What Drives Financing Decisions of SMEs? A Survey of German Bank Advisers - Marco Goeck; Ursula Walther (Credit and Capital Markets – Kredit und Kapital, 2022)
This study explores companies' financing decisions from a new perspective, those of the bank advisers, who are deeply involved in the decision processes, but are nevertheless outsiders. In our survey, corporate advisers of a large German bank report their perception of clients' decisions. The survey covers both large companies and many SMEs. It confirms the relevance of company size, but also indicates strong heterogeneity within the SMEs. While some SMEs seem to resemble large companies, others differ noticeably. Our results confirm the relevance of strategy, management experience and decision makers' personalities, but give little support for capital structure theories. The current change in German companies' financing behavior towards more market-oriented instruments is clearly visible in the responses. The core motivations seem to be a desire for financial stability and flexibility. To secure this, companies tend to combine traditional bank financing with new instruments.
Keywords: G32; G21; 330; Bank Advisors; Financing Decisions; Financing Goals; SME; Survey